Organic-Rich facies in the Sinemurian and Pliensbachian of the Lusitanian Basin, Portugal: Total organic carbon distribution and relation to transgressive-regressive facies cycles - L.V. DUARTE; R.L SILVA; L.V. OLIVEIRA; M.J. COMAS RENGIFO; F. SILVA (Geologica Acta, 2010)
The upper Sinemurian to Pliensbachian series of the Lusitanian Basin (Portugal) correspond to marly limestone sediments rich in benthic and nektonic macrofauna. This sedimentary record includes several intervals of organicrich facies, which are particularly well developed in the western sectors of the basin. They correspond to grey and dark marls locally showing strong lamination (black shale type) and are recognized as one of the most important potential oil source rocks. This study shows the vertical and lateral distribution of these organic-rich intervals, supported by over 550 total organic carbon (TOC) determinations. The results presented reveal two important intervals, with several black shale occurrences, in the Oxynotum(?)–Raricostatum (Polvoeira Member of Água de Madeiros Formation) and at the top of the Ibex-upper part of Margaritatus zones (top of the Vale das Fontes Formation), showing in the distal (western) sectors up to 22% and 15% TOC, respectively. TOC values decrease progressively towards the proximal sectors, the youngest organic-rich interval being the most expressive at the basin scale. This lateral TOC distribution, the facies stacking patterns and the decrease observed in benthic macrofauna confirm that these intervals are related to 2nd-order transgressive phases. 2nd-order regressive phases, developed during the uppermost Raricostatum and Spinatum zones respectively, show lower TOC values. TOC distribution combined with other stratigraphic and sedimentological parameters enabled seven facies maps to be created for the time interval studied. At the regional scale, this study shows for the first time the good similarity between the upper Sinemurian-Pliensbachian sedimentary successions of the Lusitanian and Basque- Cantabrian basins.